Performance Appraisal of Managerial Civil Servants Using the ANP Method and Rating Scale at the Human Resource Development Agency - Nur Atikah; R. Filia. Sari; R. Syafitri Lubis (Logaritma : Jurnal Ilmu-ilmu Pendidikan dan Sains, 2022)
Employee performance appraisal is very necessary to know the skills or abilities of each employee. Employee performance appraisal carried out at the Human Resources Development Agency still require employee performance evaluations for the performance of each employee. The purpose of this study was to determine the performance of employee using the Analytic Netwoek Process and Rating Scale methods, where the ANP was used to weight each criteria and sub-criteria with the result of the weighting ofthe criteria namely: service orientation, Integrity, commitment, discipline, cooperation  and for the weight of each sub-criterion, being friendly, completing work quickly and prcisely, working properly, honestly and regularly, working well even though not supervised by the leadership, have goog characte, have loyalty, have responsibility, do not delay work, never go absent without clear reasons, are able to work togather with colleagues, like to help colleagues who are in trouble, able to communicate well. While using the Rating Scale methods has different values, employees with the highnest to lowest performance is Rosniari, M. Arbi Suroso, Muksin, Hj. Rohayati, Syafruddin, Dame Hasibuan, Ilham Fadly and Masdalifah.